Analisa Tentang Luas Tanam dan Luas Panen di Bidang Komoditi Perkebunan di Provinsi Sumatera Barat dengan Menggunakan Analisis Profil - Wella Saputri; Nonong Amalita (UNIVERSITAS NEGERI PADANG, 2020)
Abstract—The plantation is one of the agricultural sub-sectors and an important component in the formation of the PDRB of West Sumatra Province. Crop production from plantation commodities is also supported by the planting and harvesting area. The planting area will affect into the harvesting area. In West Sumatra, there are several regions has a large amount of planting area but result in avery small amount of harvesting area. The purpose of this study is to see a comparative picture of planting and harvesting area in West Sumatra Province by using profile analysis, with ten variables of plantation commodities. Based on the results of the two population profile analysis test, the profile of planting and harvesting area of plantation commodities in West Sumatra Province were similar. There were two variables that did not have the same mean i.e. gambier and cocoa. Keywords—Planted Area, Harvested Area, Profile Analysis